Taurodontism teeth: A literature review - Haider Muneer, Tiba; Hameed Alwan, Maryam ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Taurodontism is a rare developmental dental anomaly marked by apical displacement of the pulpal floor, enlarged pulp chambers, and root bifurcation or trifurcation near the apex. Its etiology involves genetic mutations, syndromic associations, or developmental disturbances of Hertwig’s epithelial root sheath. Diagnosis relies mainly on radiographic assessment, with CBCT offering superior accuracy, and indices such as Shaw’s and Shifman’s aiding classification. Clinically, taurodontism complicates endodontic, surgical, orthodontic, and restorative procedures and may indicate underlying systemic disorders. Early recognition and interdisciplinary planning are crucial to optimizing patient outcomes. DOI: https://doi.org/10.54633/2333-024-056-030